Reiterating the Emergence of Noncoding RNAs as Regulators of the Critical Hallmarks of Gall Bladder Cancer - Varsha Rana; Dey Parama; Elina Khatoon; Sosmitha Girisa; Gautam Sethi; Ajaikumar B. Kunnumakkara (Biomolecules, 2021)
Gall bladder cancer (GBC) is a rare and one of the most aggressive types of malignancies, often associated with a poor prognosis and survival. It is a highly metastatic cancer and is often not diagnosed at the initial stages, which contributes to a poor survival rate of patients. The poor diagnosis and chemoresistance associated with the disease limit the scope of the currently available surgical and nonsurgical treatment modalities. Thus, there is a need to explore novel therapeutic targets and biomarkers that will help relieve the severity of the disease and lead to advanced therapeutic strategies. Accumulating evidence has correlated the atypical expression of various noncoding RNAs (ncRNAs), including circular RNAs (circRNAs), long noncoding RNAs (lncRNAs), microRNAs (miRNAs), and small nucleolar RNAs (snoRNA) with the increased cell proliferation, epithelial–mesenchymal transition (EMT), invasion, migration, metastasis, chemoresistance, and decreased apoptosis in GBC. Numerous reports have indicated that the dysregulated expression of ncRNAs is associated with poor prognosis and lower disease-free and overall survival in GBC patients. These reports suggest that ncRNAs might be considered novel diagnostic and prognostic markers for the management of GBC. The present review recapitulates the association of various ncRNAs in the initiation and progression of GBC and the development of novel therapeutic strategies by exploring their functional and regulatory role.